Geography of crime. Remarks on spatial analyses of crime with the use of digital technologies (Archives of Criminology, 2010)
The article discusses the issue of digital technologies use for practical applications of the principles of modern ecologic currents in criminology. The phenomenon of crime is not distributed evenly in time and space. Detailed analysis of this regularity is possible owing to crime map making. The tradition of such map making originates in the 19th century and roots from the cartographic school. Their representatives conducted analyses basing on the data coming from French police statistics. More advanced studies on spatial distribution of crime, whose authors created theoretical conceptions attempting at explaining this phenomenon, originate from the Chicago school. In our times, with the advancement of computerisation, technical capabilities of modern computers and availability of good and reliable software, crime maps are becoming an even more easily accessible and effective tool in the analysis of the phenomenon of crime. Geographic information system (GIS) is the technology currently employed for spatial analyses. It allows introducing, storing, processing and visualising geographical data. Geocoding technology enables translation to geographic coordinates and digital map making containing information on the criminal events in a given city. GIS is used in criminological analyses in two main areas: digital crime map making and geographic profiling. Crime mapping is a tool for spatial analyses of criminal incidents which consists in putting together the time and place of crime to investigate spatial patterns of criminal behaviours and hot spots. It also enables to analyse criminal incidents according to various spatial variables e.g. to compare crime scene locations with locations like bars or schools, with demographic data concerning investigated areas etc. The idea of crime mapping has its roots in theoretical assumptions of environmental criminology which seeks relations between crime and its environmental and geographic determinants. Studies on crime scene locations are related mainly to the idea of hot spots, that is places where more criminal incidents than the average are reported. Crime maps are a useful tool which enables the analysts equipped with adequate criminological knowledge to seek the reasons for concentration of criminal activity in the area. In practice, digital maps are used by the police to obtain geographical data about a given area and to manage police units. Advanced use of GIS is made in everyday work of police forces in the USA and UK. Maps can also allow the data on crime statistics on a given area to be accessed by local communities. Geographic profiling is another GIS application enabling use of criminological knowledge. It allows to establish the most likely estimated place of residence of serial offenders. A profile is made based on information concerning crime location and other places of significance to the incident (eg. place where the corpse was abandoned).